2016
DOI: 10.1016/j.radonc.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of very high-energy electron radiotherapy planning

Abstract: The dosimetric advantages of VHEE as demonstrated for a variety of clinical cases, combined with the theoretical ultra fast treatment delivery, afford VHEE scanning pencil beam radiotherapy a suitable and potentially superior alternative for cancer radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 10 publications
(20 reference statements)
0
39
0
Order By: Relevance
“…This effect seems to be accomplished through a relatively small number of beams (i.e., ~9) . The number of beams and beamlet size has also previously been investigated by our group . It was found that any increase of number of beams from the 16 beams used here and reduction in beamlet size lower than 3 mm only marginally increased the VHEE plan performance, and the use of 16 beams with 3 mm beamlet size was found to be optimal when also considering future machine layouts.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This effect seems to be accomplished through a relatively small number of beams (i.e., ~9) . The number of beams and beamlet size has also previously been investigated by our group . It was found that any increase of number of beams from the 16 beams used here and reduction in beamlet size lower than 3 mm only marginally increased the VHEE plan performance, and the use of 16 beams with 3 mm beamlet size was found to be optimal when also considering future machine layouts.…”
Section: Discussionmentioning
confidence: 56%
“…The generation of the VHEE beams has been described elsewhere . Briefly, the VHEE pencil beams were calculated in the Monte Carlo EGSnrc/DOSXYZnrc code for 100 and 200 MeV beams through an in‐house developed graphical user interface in Matlab (The Mathworks, Nattick, MA, USA), which has been previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Palma et al . [ 17 ] reported that the most favorable equivalent uniform doses and lowest doses to organs at risk were achieved with variable dose rate VMAT, which was statistically significantly better than 5-field, step-and-shoot IMRT for rectal and femoral head dosimetric endpoints and better than constant dose-rate VMAT for most bladder and rectal endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…15,23 The present research on VHEEs aims to investigate technical features, treatment quality, delivery and manipulation of VHEEs. [24][25][26][27] To improve dose distribution and examine the radiobiological effectiveness (RBE) of VHEEs have yet to be explored. Figure 1 presents Monte Carlo calculated percentage depth dose (PDD) curves in 30 × 30 × 30 cm 3 water phantom for various types of radiation with 10 × 10 cm 2 field size.…”
Section: Introductionmentioning
confidence: 99%